Diplomasi Budaya India melalui Yoga di Indonesia Tahun 2014-2019 - Kesuma Wijaya, Putu Pradnya Sri; Suwecawangsa, Adi P.; Kawitri Resen, Putu Titah (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2021)
During the reign of Prime Minister Narendra Modi, India’s Government more focused on the use of ancient Indian culture as a tool of cultural diplomacy. Yoga is one of cultures used as a tool of Indian cultural diplomacy to various countries in the world. The values of peace and harmony and the many benefits for each individual contained in Yoga made the Indian government realize the potential of Yoga as a tool to embody India’s national interest. Indonesia is one of India’s destination countries for Yoga diplomacy. Indian Yoga diplomacy in Indonesia certainly has an interest in it. This research uses the framework of cultural diplomacy and national interests at soft power to answer the interests of India in performing cultural diplomacy through Yoga in Indonesia in 2014-2019. This research then finds that India’s interests in Indonesia through Yoga diplomacy is economic interests especially in the tourism and commerce.   Keyword : Yoga India, Indonesia, cultural diplomacy, national interests